ANALISIS FAKTOR WISATAWAN NUSANTARA MEMBELI TIKET PESAWAT KE BALI - Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
The increasing number of airlines that provide flight routes to Bali, causes tourists to consider various factors before making the purchase of an airline ticket that would be used to go to Bali. This study aims to determine the factors that influence the decision of domestic tourists to purchase airline tickets to Bali with a quantitative descriptive approach. Data collected through observation, questionnaire distribution, and literature study. The sample in this study amounted to 100 tourists who were obtained accidentally. With the help of factor analysis using SPSS version 17, out of 26 indicators, six major factors were formed that influenced the behavior of domestic tourists in purchasing airline tickets to Bali, including: psychological factor, social factor, cultural factor, marketing mix factor, employment factor, and personal factor. The dominant factor that has influenced the behavior of domestic tourists in purchasing tickets is psychological factors with an eigenvalue of 14.135 and a variance percentage of 42.832%. As for forming psychological factors, airline image factors got the biggest loading factor which is a number of 0.881.